2021
DOI: 10.3390/ijms222111316
|View full text |Cite
|
Sign up to set email alerts
|

β-Barrels and Amyloids: Structural Transitions, Biological Functions, and Pathogenesis

Abstract: Insoluble protein aggregates with fibrillar morphology called amyloids and β-barrel proteins both share a β-sheet-rich structure. Correctly folded β-barrel proteins can not only function in monomeric (dimeric) form, but also tend to interact with one another—followed, in several cases, by formation of higher order oligomers or even aggregates. In recent years, findings proving that β-barrel proteins can adopt cross-β amyloid folds have emerged. Different β-barrel proteins were shown to form amyloid fibrils in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 253 publications
2
13
0
Order By: Relevance
“…Thus, an increase in the RopB production is associated with free-living cellto bacteroid transition but RopB amyloids form at different stages of bacteroid development suggesting their functional role in this process. These observations are in line with other studies demonstrating the amyloidogenic properties of different b-barrel proteins (Sulatskaya et al, 2021). Another b-barrel protein whose detergent-resistant aggregates are detected in the root nodules is vicilin, a seed storage protein of P. sativum L., that contains two ancient cupin b-barrel domains (Bäumlein et al, 1995;Shutov et al, 1995).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, an increase in the RopB production is associated with free-living cellto bacteroid transition but RopB amyloids form at different stages of bacteroid development suggesting their functional role in this process. These observations are in line with other studies demonstrating the amyloidogenic properties of different b-barrel proteins (Sulatskaya et al, 2021). Another b-barrel protein whose detergent-resistant aggregates are detected in the root nodules is vicilin, a seed storage protein of P. sativum L., that contains two ancient cupin b-barrel domains (Bäumlein et al, 1995;Shutov et al, 1995).…”
Section: Discussionsupporting
confidence: 91%
“…Soybean 7S protein is a heterogenic trimer, and all three α, α′, and β subunits share the common core region with conserved bi-cupin structures that can adopt the β-barrel conformation. 36 In recent years, accumulated studies have found that many β-barrel proteins form amyloids in vivo for interspecies interactions and nutrient storage 24 for which the native pea vicilin is the amyloid state was also discovered. 23 Therefore, it is more likely that soybean 7S protein contains amyloid aggregates, and pepsin digestion might further facilitate amyloid aggregation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…23 Vicilin contains conserved β-barrel structures that could be easily self-assembled into amyloid aggregates or fibrils in vivo and in vitro. 24 They also demonstrated that the garden pea amyloid aggregates exhibited digestion resistance to GI enzyme proteolysis and even tolerance to detergent treatment, which depended on the aggregation state. 23 The accumulation of storage protein in amyloid aggregates during seed maturation may be critical for plant seeds to endure extreme conditions (e.g., desiccation and freezing) for long-term survival since these structures are thermodynamically stable, resistant to protease hydrolysis, and thus exhibit poor digestibility to predator insects and animals.…”
Section: ■ Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…These results support our proposal that Aβ42 channels contain β-barrels resembling those we proposed for oligomers and APFs. (6) The hypothesis that numerous amyloid oligomers have β-barrel structures and evidence that various β-barrel proteins can form amyloid structures has gained popularity (see Sulatskaya et al 44 for a recent review).…”
Section: Qklvffaedvgsn Aβ 17-27mentioning
confidence: 99%